2020
DOI: 10.1093/ajcp/aqaa266
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analyses Associate Hemostasis Activation Biomarkers With Poor Outcomes in Patients With COVID-19

Abstract: Objectives Patients with coronavirus disease 2019 (COVID-19) have thromboembolic complications. Assessment of coagulation and other markers could be useful to understand their coagulopathy. Methods We performed a retrospective study of inflammatory and coagulation parameters, including prothrombin fragment 1.2 (PF1.2), thrombin-antithrombin complexes (TATs), fibrin monomers, and D-dimer, in hospitalized patients with COVID-19. We compared the markers in patients with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(21 reference statements)
0
7
0
2
Order By: Relevance
“… 8 , 22 In our institution, the MOCHA panel in patients with COVID-19 showed that elevation in PF1.2 and TAT was associated with admission to the ICU, while D-dimer and fibrin monomers were increased in patients with poor outcomes. 14 Clinicians find value in the panel and its interpretation, as evidenced by the continued ordering of the panel for patients with cardiac conditions, including use of repeated measures. Though, it was not clear from our review of charts what triggers physicians to repeat testing in some patients but not others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 22 In our institution, the MOCHA panel in patients with COVID-19 showed that elevation in PF1.2 and TAT was associated with admission to the ICU, while D-dimer and fibrin monomers were increased in patients with poor outcomes. 14 Clinicians find value in the panel and its interpretation, as evidenced by the continued ordering of the panel for patients with cardiac conditions, including use of repeated measures. Though, it was not clear from our review of charts what triggers physicians to repeat testing in some patients but not others.…”
Section: Discussionmentioning
confidence: 99%
“…We have used the panel to study patients with stroke 13 and during the SARS-CoV2 pandemic. 14 The great majority of the MOCHA panel results from patients from the cardiology service are abnormal and the 4 conditions for which they are ordered include presence of heart assist devices, cardiomyopathies, atrial fibrillation, and intracardiac thrombosis. The objective of this study was to identify the variations present in MOCHA panel parameters for the above 4 conditions and perform a correlation with anticoagulation treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Outros autores também verificaram a alta concentração do D-dímero em pacientes com COVID-19 e TV (PELLEGRINE et al, 2021;KERBIKOV et al, 2020;MOTAGANAHALLI et al, 2021). Outros resultados estatisticamente significativos incluem contagens de leucócitos anormais e proteína C reativa elevada, associados com admissão dos pacientes na UTI (MOOSAVI et al, 2020;POILLON et al, 2020). Bem como, a elevada taxa de enzimas hepáticas, do nível sérico de lactato desidrogenase (LDH) de acordo com os estudos de Motaganahalli et al (2021)…”
Section: Discussionunclassified
“…1 for each patient. The maximal FRM levels (medians) observed before censoring (TE, death, ICU discharge or end of study period) were higher in patients diagnosed with a TE than in patients who were not: 20,000 (IQR: 7,610–20,000) versus 3710 ng/mL (2,825–6,265) for D-dimers ( p = 0.009, Mann-Whitney U test); 139 (8–150) versus 10 μg/mL 4 5 6 7 8 9 10 11 12 13 14 15 16 for FM ( p = 0.05, Mann-Whitney U test). We arbitrarily defined peak levels as follows: above 15,000 ng/mL or 100 μg/mL for D-dimers and FM respectively.…”
Section: Figmentioning
confidence: 97%
“… 10 To the best of our knowledge, there are few available data on FM in COVID-19 patients. 11 12 We therefore undertook a prospective observational exploratory monocentre study to get some insight as to whether their serial monitoring might help suspect an on-going thrombosis.…”
Section: Figmentioning
confidence: 99%